2011
DOI: 10.1590/s0366-69132011000400011
|View full text |Cite
|
Sign up to set email alerts
|

Influência do Y2O3 na sinterização rápida de mulita comercial

Abstract: têm tido e continuam tendo um papel significante no desenvolvimento de cerâmicas tradicionais e avançadas [1]. A mulita (3Al 2 O 3 .2SiO 2 ) é um dos materiais cerâmicos mais importantes e extensivamente estudados [2], tendo tornado-se nos últimos anos um grande candidato para as cerâmicas avançadas estruturais e funcionais. As razões para esse desenvolvimento são suas excelentes propriedades: baixo coeficiente de expansão térmica, baixa condutividade térmica e grande resistência a fluência. Outras característ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Mullite is a refractory ceramic of great industrial importance because of its variety of applications since it can be used in traditional applications such as dishes and refractory products as well as in advanced ones, including structural and functional applications [1][2][3][4][5]. Such versatility is because of its properties, namely: low thermal conductivity, low thermal expansion coefficient, hightemperature resistance, good chemical stability, low density (3.18 g/cm 3 ), excellent creep and thermal shock resistance, high melting point, and excellent electrical resistance [1,2,[5][6][7][8][9][10]. In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Mullite is a refractory ceramic of great industrial importance because of its variety of applications since it can be used in traditional applications such as dishes and refractory products as well as in advanced ones, including structural and functional applications [1][2][3][4][5]. Such versatility is because of its properties, namely: low thermal conductivity, low thermal expansion coefficient, hightemperature resistance, good chemical stability, low density (3.18 g/cm 3 ), excellent creep and thermal shock resistance, high melting point, and excellent electrical resistance [1,2,[5][6][7][8][9][10]. In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…In the Al 2 O 3 -SiO 2 phase diagram, mullite is the only stable crystalline phase up to around 1800 ºC under atmospheric pressure [8][9][10][11]. However, due to its high covalent bond degree, and slow diffusion of the Al 3+ and Si 4+ ions in the mullite network and grain boundaries, its production requires high temperatures, above 1600 ºC, and long sintering times to achieve good densification [2,3,6,7,9]. Atisivan et al [12] reported that mullite densification was observed at high temperatures, around 1650 ºC.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 3: SEM micrographs showing: mullite crystals in porcelains sintered at 1350 °C (a,b); mullite samples (density 95%) sintered in microwave oven (1.5 kW, 16 min) (c) and conventional oven (high vacuum) at 1650 ºC/2 h (d)[29]; mullite samples sintered at 1600 °C with heating rates of 5 °C/min (density 90%) (e) and 80 °C/min (density 78%) (f)[30].…”
mentioning
confidence: 99%